Pengaruh Persepsi Kebermanfaatan, Kepercayaan Dan Computer Self Efficacy Terhadap Niatan Menggunakan E-Banking Pada Mahasiswa - Bella, Hannum Sansa, Fauzan, SE., M.Si, Shinta Permata sari, SE (2014)
The aim of this study is to find out technology acceptance of E-banking among undergraduate students. Thus, the theoretical framework of the study is based on modified version of Technology Acceptance Model (TAM). This study develops a technology acceptance model for E-banking, a conceptual framework to explain the factors influence undergraduate students' acceptance of E-banking. The model focus on perceived usefulness, trust and computer self-efficacy. The first one is an initial constructs of TAM model. And the others are new constructs in order extend TAM model that are better reflects the students' view. This research was conducted at Economic and Business Faculty Universitas Muhammadiyah Surakarta with a purposive sampling method. This study gets 150 respondents who are undergraduate student of accounting majors and want to use E-banking. Data obtained using the questionnaire method. Data is analyzed with multiple regression analysis. The result of this research show that perceived usefullness, trust and computer self efficacy tend to have effect on intention to use E-banking.